LEADERSHIP MANAGEMENT OF SCHOOL PRINCIPALS, TEACHER PROFESSIONALISM AND COMMUNITY PARTICIPATION IN IMPROVING THE QUALITY OF EDUCATION AT SMK IT MADANI BAROS, SUKABUMI CITY - Raudatul Janah; Mulyawan Safwandy Nugraha (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Based on the whole description of the principal's management, teachers' professionalism and the community's participation in improving the quality of teaching in this school, it can be concluded from the research results that the educational program organized by the school organization is basically very successful. it is difficult to achieve if the opinions of the principal, teachers and the community about the real meaning of education and the implementation of the educational process in schools are not harmonized. Therefore, school leaders in this case the principal, teachers and the community must work in an integrated manner to achieve each educational goal. Forming the next generation of quality in terms of knowledge, skills and attitudes. When we talk about education, the first thing that comes to mind is "school". Schools in this case are public organizations that provide educational services to the community to improve the quality of individuals in the community. Therefore, it is natural that the community demands a "good school", which is reflected in school performance. Here, school education quality management requires principal leadership, teacher professionalism and optimal community participation from the results of research at SMK IT MADANI BAROS CITY SUKABUMI. This research is a descriptive qualitative research that finds, discovers and explores knowledge about the principal's leadership, teacher professionalism and community participation in improving the quality of education at SMK IT MADANI BAROS SUKABUMI, based on the results of interviews with the high school principal that the principal of SMA Madani Baros has tried to improve the quality of learning by always holding regular meetings once a week and checking teacher attendance to monitor the fulfillment of the vision and mission of SMA Madani Baros sukabumi, the principal also motivates teachers and motivates teachers to participate in workshops. SMA Baros Madan sukabumi teacher professionalism, community participation at SMA Baros Madan Sukabumi is very supportive of the existence of this school and the school also received responses and votes from the surrounding community and the existence of SMA Baros Madan is very good community support. because there is only one high school.